Divine interpretation: studies in medieval and modern hermeneutics - Torrance, Thomas F. (Thomas F. Torrance collected studies., 2017)
By publishing these essays together for the first time, this collection widens access to a number of T. F. Torrance's illuminating studies on the history of biblical hermeneutics. Moreover, by detailing Torrance's extensive engagement with primary sources, which generally appear only in summary form across his writings, this collection reveals to readers how Torrance's own theological hermeneutics were forged through deep fellowship with the communion of the saints